Modern feminist thought : from the second wave to "post-feminism" - Whelehan, Imelda, 1960- (Rawat, 2015)
1. Liberal Feminism: The Origins of the Second Wave -- 2. Marxist/Socialist Feminism: Reconstructing Male Radicalism -- 3. Radical Feminism: Redefining Politics -- 4. Lesbian Feminism: Exploding 'Heteroreality' -- 5. Black Feminism: Reimagining 'Equality' -- 6. Crisis in Feminism?: Feminist Debates in the '80s and '90s -- 7. Sites of Fissure: Putting the Politics of the Personal to the Test -- 8. Men in Feminism -- 9. Feminism, Postmodernism and Theoretical Developments -- 10. Identity Crisis?: 'Post-feminism', the Media and 'Feminist Superstars'.